Analisis Kebijakan Penataan Sistem Transportasi Perkotaan (Studi Kasus Di Kota Bandung) - Yudiantarti Safitri; Rosita Novi Andari (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2011)
Structuring Urban Transportation System in Indonesia is an important problem to overcome. The enactment of Law no. 22 year 2009 regarding Road Traffic and Road Transportation is the one of government's commitment in arranged system of transportation. Bandung City as one of Metropolitan Cities in Indonesia is also facing a complex transportation problems. Based on the research, the availability and adequacy of transportation facilities and infrastructure are still inadequate to satisfy the society. Public transportation in Bandung City is not comfort and safety yet. The levels of comfort and safety of transportation infrastructure are still low and the shelter needs becomes quite important. Meanwhile, levels of security and comfort of other transportation infrastructure such as parking and terminal are also considered low. To fulfill the availability and feasibility of transportation infrastructure, the local government has been implementing various policies such as Local Regulation no. 2 year 2008 regarding Implementation of Transportation in Bandung, since some regulatory barriers such as lack of clarity and authority, lack of coordination among relevant agencies and low public awareness of the utilization of transportation facilities and infrastructure, causes implementation of the regulation is not optimal.